Molecular epidemiology and antimicrobial susceptibility of Clostridium difficile isolated from the Chinese People's Liberation Army General Hospital in China. (February 2018) - Wang, Rui; Suo, Lin; Chen, Hui Xia; Song, Lin Jian; Shen, Yue Yun; Luo, Yan Ping
Highlights: The glutamate dehydrogenase (GDH) test and anaerobic culture were employed to screen for Clostridium difficile in the stool samples of 280 adult patients. All isolates were susceptible to vancomycin. Multidrug resistance was detected in one non-toxigenic strain, belonging to sequence type ST-109. The Ala97Ser mutation in gyrA and the Asp426Ala mutation in gyrB are novel mutations found in this study. Abstract: Clostridium difficile is a Gram-positive, spore-forming obligate anaerobe responsible for antibiotic-associated diarrhoea. Its virulence is associated with the production of endotoxins A and B and endospores, which can cause symptoms, such as diarrhoea, toxic megacolon, and pseudomembranous colitis. Given the increasing elderly population and the well-recognized problem of over-prescribing of broad-spectrum antibiotics, it is critical to have an understanding of molecular epidemiology and antimicrobial susceptibility in China. This study analyzed the toxin types and multilocus sequence typing (MLST) results of 74 clinical isolates of C. difficile after the glutamate dehydrogenase (GDH) screening test and anaerobic culture. The minimum inhibitory concentrations (MICs) of four different antibiotics were determined for all of the isolates, and the bacterial resistance mechanisms were investigated. Sixty-five strains (75%) were toxigenic, including 54 tcdA -positive, tcdB -positive, and cdtA / cdtB -negative strains (A + B + CDT − ) and nine A − B + CDT − strains. Eleven strains (14.9%) were non-toxigenic. All clinical isolates were classified into 26 MLST genotypes, with the predominant type being ST-54 (18.9%). All isolates were susceptible to vancomycin. The tetracycline, clindamycin, and levofloxacin resistance rates were 1.4%, 36.5%, and 20.3%, respectively. The expression of tet (M), erm (B), and mutations of g yrA and/or gyrB were observed in the tetracycline-, clindamycin-, and levofloxacin-resistant isolates, respectively.